Carbon contracts for difference as an instrument for strengthening climate cooperation between industrialized and emerging economies - Heiner von Lüpke; Catherine Marchewitz; Karsten Neuhoff; Charlotte Aebischer; Mats Kröger (DIW Weekly Report, 2022)
Industrialized countries and emerging economies must cooperate in order to decarbonize the emissions-intensive industrial sector and to limit global warming to 1.5 degrees Celsius. While Germany and the other G7 countries have committed to supporting emerging economies in their efforts to combat climate change via international climate finance, it remains to be seen how this support can be implemented successfully. A wide variety of cooperation initiatives that could form a foundation for climate financing - such as climate clubs, partnerships, and alliances - are currently being discussed. However, the incentives to cooperate are not the same for industrialized and emerging countries. As of 2022, the climate club discourse centers on carbon prices, a carbon border adjustment mechanism, incentives for club membership, and sanctions for non-compliance. Financial-technical support for emerging countries has not been discussed sufficiently. Building on interviews with steel sector representatives, international organizations, the financial sector, and think tanks from both the European Union and emerging and developing countries, this paper analyzes existing gaps in cooperation. Moreover, it discusses how international carbon contracts for difference (CCfDs) can support the decarbonization of the steel industry.
Keywords: Q40; Q41; Q42; Q48; F3; F63; F65; 330; climate policy; international climate finance; cooperation; decarbonisation